Deliver us from evil - Baldacci, David (New York : Grand Central Pub., 2010)
Evan Waller is a monster and his latest business venture could lead to millions of deaths all over the globe unless he can be stopped by two mysterious operatives who are unaware of each other's mission.
Sequel to: The whole truth by David Baldacci.
Keywords: Women journalists -- Fiction; International relations -- Fiction; Large type books; Spy stories; Suspense fiction